Performance of Soil Quality: Indicator-Based GIS Analysis of Jamuna-Dhaleshwari and Surma-Kushiyara Floodplain Regions, Bangladesh - Tanbi Tanaya Sarker; Sameena Begum; Md. Shohel Khan; Mohammed Abdus Salam; Shehan Tawsif (Department of Geography Education, University of Jember, 2022)
Bangladesh is an agriculture based economic country formed by sediment deposition from upstream rivers. This riparian country covered with fertile soil that supports agricultural diversification. The study aimed to compare current soil quality of Jamuna-dhaleshwari (Manikganj) and Surma-kushiyara (Sylhet) floodplain physiographic regions to forecast about agricultural productivity. Soil quality was assessed through physical (soil texture and moisture), and chemical (pH, electrical conductivity (EC), salinity, soil nutrients (N, P, K), and organic matter content) indicators. A total of 36 soil samples in three different depths (0-15cm, 15-50cm, 50-100cm) from 12 sites were collected from Manikganj and Sylhet Districts. The average particle size and moisture content ratios of Manikganj: Sylhet were gravels (7.88:5.8), very coarse sand (6.85:8.53), coarse sand (7.45:13.2), medium sand (7.35:14), fine sand (6.12:16.4), very fine sand (24.3:19.9), silt (39.56:20.57), and clay (29.3:32.81), followed by, pH (7.61:6.31), and EC (0.24:0.18), respectively. The result revealed that the soil was bit alkaline for Manikganj, compared to range from alkaline to acidic in Sylhet and non-saline for both areas that was suitable for agriculture. The average concentration of nitrogen (N), phosphorous (P), potassium (K) nutrients in Manikganj and Sylhet Districts were 0.14%, 3.73 meq/100g, 0.07 Âµg/g; 0.16%, 3.11 meq/100g, 0.08 Âµg/g and organic matter were 3.65% and 4.7%, respectively. The results of nutrients in both areas indicated that nutrients were very poor but soil organic matter content was sufficient for agricultural activities. The study concluded that soil texture, pH, salinity and organic matter content in both areas were suitable for agricultural purposes, but a significant declined was found in soil moisture and nutrients quality. Finally, it was recommended that soils of Manikganj were more sustainable for agricultural activities. Keywords : Soil quality; soil texture; organic matter; spatial distribution Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License